2004
DOI: 10.1001/archsurg.139.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Teaching Status and Outcomes of Complex Surgical Procedures in the United States

Abstract: Hypothesis: Complex operations performed in teaching hospitals have similar outcomes as those performed in nonteaching hospitals.Design: Observational cohort study with clinical patient data obtained from the Nationwide Inpatient Sample. The Nationwide Inpatient Sample data were linked to the American Hospital Association hospital survey data for 1997 to determine hospital characteristics. Hospitals were considered high volume if they performed more than the median (50th percentile) number of procedures per ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(124 citation statements)
references
References 16 publications
5
114
2
1
Order By: Relevance
“…The precise reason for this is unknown, but it has been suggested that teaching hospitals benefit from increased surgeon experience, advanced training, availability of intensive care unit staffing, availability of diagnostic technology, and other factors. 5 Last, mortality was not significantly different between groups (0.4% in teaching hospitals and < 0.4% in nonteaching hospitals, p = 0.210), which was consistent with findings in previous studies. 6,12 Although the results of the present study suggest that ASD surgery may be safer in teaching versus nonteaching hospitals, redirecting patient care may not be entirely feasible, and more studies are needed before definitive conclusions can be made.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The precise reason for this is unknown, but it has been suggested that teaching hospitals benefit from increased surgeon experience, advanced training, availability of intensive care unit staffing, availability of diagnostic technology, and other factors. 5 Last, mortality was not significantly different between groups (0.4% in teaching hospitals and < 0.4% in nonteaching hospitals, p = 0.210), which was consistent with findings in previous studies. 6,12 Although the results of the present study suggest that ASD surgery may be safer in teaching versus nonteaching hospitals, redirecting patient care may not be entirely feasible, and more studies are needed before definitive conclusions can be made.…”
Section: Discussionsupporting
confidence: 92%
“…Commensurate with our findings, other studies have found better outcomes in teaching hospitals for more complex procedures such as lung cancer resection, abdominal hysterectomy, pancreatic resection, hepatic resection, and esophageal resection. 5,8,11 Given that ASD surgery may be considered more complex than an anterior cervical discectomy and fusion or a posterior lumbar laminectomy and fusion, this could explain the conflicting results with those of the studies by Fineberg et al and Nandyala et al, which examined the latter procedures. Furthermore, 4.7% of all procedures in our study were found to be revision procedures; 21.0% involved fusion of 8 or more segments; and 25.1% were categorized as complex ASD procedures, involving fusion of 8 or more segments or osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression models were used to assess the association of opioid abuse and dependence with predetermined study endpoints: inpatient mortality and adverse events, failure to rescue (death after an adverse event) [21], prolonged LOS ([ 75th percentile for each procedure) [15], and nonroutine discharge (discharged to a location other than home). All covariates (patient demographics, individual comorbidities, hospital characteristics, and procedure type) were defined a priori and entered into the models simultaneously without further selection.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Discrepancies in patient outcomes also lie in the hospital characteristics, with high-volume and teaching hospitals providing better quality care. 6,7 An integral aspect of surgical care in teaching hospitals is resident involvement. 8 In urologic surgical training, minimally-invasive techniques are an important part of surgical training, and resident participation is common and expected, as the demand for minimally-invasive procedures continues to grow.…”
Section: Introductionmentioning
confidence: 99%